The effect of intravenous insulin, apheresis and oral lipid-lowering agents on non-fasting hypertriglyceridemia and associated pancreatitis. Issue 5 (4th July 2018) - Frankova, Daniela; Olson, Kristin Melissa; Whyms, Brian Joseph; Guevara Hernandez, Maria Alejandra; Franko, Jan
ABSTRACT: Objectives: There is evidence that increasing severity of hypertriglyceridemia increases the risk of acute pancreatitis. There is a debate about superiority of treatment methods and previous works have specifically called for direct comparison between IV insulin and apheresis techniques. Identify patient characteristics predictive of lipid-lowering therapy selection in a large community hospital for treatment of hypertriglyceridemia; evaluate for a concentration-dependent relationship between hypertriglyceridemia severity and risk of acute pancreatitis; assess for differences in clinical outcomes between patients treated with IV insulin versus apheresis. Methods : Single center, retrospective cohort study including patients with hypertriglyceridemia between January 2007 and December 2016. Main measures included frequency of pancreatitis, choice of lipid-lowering therapy, and clinical comparisons of diet, oral lipid-lowering agents, IV insulin, and apheresis. Results : Initial serum triglyceride level and disease acuity was higher among patients in insulin and apheresis groups. Neither triglyceride level, Charlson comorbidity index, age, BISAP score, nor initial CRP predicted use of IV insulin versus apheresis. Prevalence of pancreatitis increased with higher triglyceride level, reaching 48% with triglycerides >2000 md/dL (p < 0.001). There was a significant decrease in serum triglycerides at each time interval (p < 0.05) in patients treated with IV insulin and apheresis, but no difference in clearance rate between the two. Length of stay did not differ between IV insulin and apheresis. Conclusion : The presence of pancreatitis, hyperglycemia, and hypertriglyceridemia severity influenced selection of therapies like IV insulin and apheresis. We found no superiority of either IV insulin or apheresis in the treatment of severe hypertriglyceridemia among patients hospitalized for pancreatitis.